Dos modalidades de transmisión de la Identidad Judía: la Shoa y Jabad - Hamui Sutton, Liz (Cuadernos Judaicos, 2008)
The analysis of two actual strategies in the reformulation of the J ewish identity in Israel and the diaspora, are the central themes of this article. The historie memory ofthe Hebrew people in cognitive and emotional terms affirms the collective commitment with Judaism. One ofthe strategies is secular and the other religious. The first is based on ¡he transmission of¡he Shoa (Holocaust) to the new generations as an exemplary event experienced by the Jews Ihat pretends not to be forgotten lo avoid its recurren ce in other groups. The message has a universal dimension that incrusts in the Jcwish hislory wilhin the westem culture and reinforee secular values sueh as democracy, tolerance, respecI lo olhers, pluriculturalism and social justice. In the Jabad case, by the theological way, Ihe objective is the relígious re-enchanlment of Ihe world in all Ihe aspects of life lo create a social milieu that emJlates what they consider the authentie Judaism inspired in the shtetI, the premodem commu¿ities of the ashkenazi Jews in Eastem Europe. In both cases, the historical and cultural legacy acquire new meanings that summon Jews, giving conlinuity lo Judaísm.